Building a more intelligent enterprise - Schoemaker, Paul J. H.; Tetlock, Philip E. (Philip Eyrikson), 1954- (MIT Sloan Management Review, 2017)
To succeed in the long run, businesses need to create and leverage some kind of sustainable competitive edge. Although the authors say that advantages can still come from sources such as lower cost, intellectual property, motivated employees, and strategic leaders, they argue that in the knowledge economy, strategic advantages will increasingly depend on a capacity to make superior judgments and choices. Intelligent enterprises today are being shaped by two distinct forces. The first is the growing power of computers and big data, which provide the foundation for operations research, forecasting models, and artificial intelligence. The second is our growing understanding of human judgment, reasoning, and choice. Decades of research has yielded deep insights into what humans do well or poorly. In this article, the authors examine how managers can combine human intelligence with technology-enabled insights to make smarter choices in the face of uncertainty and complexity and thus gain a cumulative advantage in business. They note five strategic capabilities that intelligent enterprises can use to develop an advantage over competitors: 1. Find the strategic edge. In assessing past organizational forecasts, home in on areas where improving subjective predictions can really move the needle. 2. Run prediction tournaments. Discover the best forecasting methods by encouraging competition, experimentation, and innovation among teams. 3. Model the experts in your midst. Identify the people internally who have demonstrated superior insights into key business areas, and leverage their wisdom using simple linear models. 4. Experiment with artificial intelligence. Use deep neural nets in limited task domains to outperform human experts. 5. Change the way the organization operates. Promote an exploratory culture that continually looks for better ways to combine the capabilities of humans and machines. Reprint 58301. For ordering information, see page 4.